Strategi Pemerintah dan Masyarakat dalam Meningkatkan Daya Tarik Wisata Arung Jeram Ampalu - Ratna; Rika Despica; Rozana Eka Putri (Geography Education Study Program, Universitas Kanjuruhan Malang, 2026)
This research aims to analyze the government's and community's strategies in increasing the attractiveness of Ampalu rafting tourism. The approach used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The research informants include the Tourism Office, tourism managers, local communities, and tourists. The results of the study show that the government plays a role in fostering human resources, promoting destinations, and providing supporting facilities and infrastructure, although it is not fully optimal. Tourism managers develop attraction through the use of natural potential and the application of the Sapta Pesona principle to improve the quality of services and tourism experiences. The community actively participates in supporting tourism activities, maintaining a clean environment, and providing support services that contribute to the improvement of the local economy. Synergy between the government, managers, and the community is the main factor in the development of Ampalu rafting tourist destinations. The obstacles faced include limited facilities, accessibility, and promotion that has not been maximized. This research recommends improving infrastructure, strengthening digital-based promotions, and developing the capacity of human resources to realize sustainable and competitive tourism.